The Role of Legal Sociology in Terms of Covid-19: Large-Scale Social Restrictions (PSBB) in Indonesia - Rahayu Hartini1 , Yusufa Ibnu Sina Setiawan2 (Institute of Medico-legal Publications Pvt Ltd, 2021)
The study of legal sociology is a study that has legal phenomena, but uses social science and sociologytheory. The role of Legal sociology is so tight when juxtaposed with a problem that is emerging, namelythe global pandemic Coronavirus Disease (Covid)-19. The juridical normative research with a method ofapproach to the law, conceptual and comparative. Legal materials that have been collected are analyzed bycontent analysis. Some affected countries that successfully handled the COVID-19 pandemic, including:South Korea, New Zealand, Singapore. Italy and United States containment strategy for handling Covid-19are contradictory from those countries above. PSBB has been applied in Indonesia and other countries. ThePSBB must be accompanied by other programs so that the government can successfully handle COVID-19..PSBB does not guarantee that the community will obey the regulation. The most effective action with allthe consequences is regional quarantine or lockdown accompanied by other supporting programs from thegovernment.